The Development of Islamic Religious Education Curriculum (PAI) for Internected Citizens (Prisonesrs) in Class I State Prison House, Cirebon City - suklani Suklani; A Syathori; Imam Sibaweh (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2022)
The purpose of this study relates to the state detention house which is basically a home for inmates who have committed criminal acts, perpetrators of crimes with various actions. However, the researcher analyzed that they had lost their way in life. So, it is not kept away but given a humanitarian approach. A powerful humanitarian approach by providing education to them. The approach to Islamic religious education is the bulwark of morality in their lives after leaving the detention center. Researchers divide Islamic religious education into five aspects, namely: (1) iqro, (2) fiqh, (3) moral aqidah, (4) quran hadith, (5) cultural history, and (6) deepening of the Koran. The researcher concludes: (a) the implementation of adding material is important, measuring the success of education, adequate teaching staff, (b) the curriculum must be standard, the material still depends on the ustad, the material is in accordance with the respective cleric's ormas, and (c) there are several obstacles inmates who are difficult to take to class, lazy to learn and low motivation from inmates, lack of teaching staff and incomplete facilities.